How does the ICD recognize the type of arrhythmia? Tachyarrhythmia discrimination in modern transvenous cardioverter defibrillators - Flóra Diána Gausz; Zsolt Bári; Máté Vámos (Cardiologia Hungarica, 2025)
Modern cardioverter defibrillators apply different discrimination algorithms to differentiate between supraventricular arrhythmias and malignant ventricular arrhythmias, leading to a decrease in the rate of inappropriate ICD therapies. The two main groups of discrimination algorithms are single-chamber and dual-chamber configurations. Single-chamber discriminators analyze only ventricular signals, while dual-chamber algorithms evaluate both ventricular and atrial activity. While different ICD devices distinguish between arrhythmias based on fundamentally similar criteria, the several various, manufacturer-based programming options allow for several configurable discrimination settings. The aim of this review article is to describe the essential single- and dual-chamber discrimination algorithms, emphasizing the main differences between the most commonly used devices nowadays in Hungary.